The employee's job satisfaction during pandemic covid-19 and the counselor's role - Zadrian Ardi; Mharchelya Mharchelya; Ifdil Ifdil (RedWhite Press, 2021)
Many employees can not work as usual, even having to lose work due to the Covid-19 Pandemic. Generally, employees have difficulty adapting to the demands that all are done at home or better known as Work From Home. In this situation, employees need to continue to work in the company or its organization while paying attention to health protocols that the Government has established. However, this has an impact on job satisfaction and employee mental health. This manuscript analyzes the impact of the pandemic on employee performance and the role of counselors in optimizing mental health. Many employees feel that their work must be more extra to meet the needs of life to be fulfilled and how the level of work satisfaction of the employees themselves in the face of this COVID-19 pandemic. Here also required an expert or counselor to know the job satisfaction of the employees themselves so that they can still provide services or the best results for the company and himself.